Interviste di Massimo Fagioli a Rai News 24 - Fagioli, Massimo (Il sogno della farfalla, 2017)
A few interviews Massimo Fagioli gave between 2001 and 2013 and which were broadcast on Rai News 24 TV channel have been reported here. With the journalists Piero Di Pasquale, Carlo De Biasio and Francesco Gatti, Massimo Fagioli speaks about his books and his way of writing, introduces his Human Birth Theory and discusses not only about the current state of psychiatry but also current cultural and political hot topics.